Experimental Method Improves Psychomotor Skills in Natural Science Learning: Metode Eksperimental Meningkatkan Keterampilan Psikomotor dalam Pembelajaran Ilmu Pengetahuan Alam - Nurhayati, Hanik Oktaviya; Sartika, Septi Budi; Salim, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education plays a crucial role in developing students’ cognitive, affective, and psychomotor domains, with psychomotor skills being essential for practical science learning. Specific Background: In elementary science education, instructional practices often emphasize cognitive knowledge, leaving psychomotor skill development underexplored. Knowledge Gap: Limited research addresses effective strategies for enhancing psychomotor abilities in primary school science contexts. Aims: This study aimed to improve the psychomotor skills of 4th grade primary school students in natural science learning through the application of the experimental method. Results: Using a weak-experimental design with one group pretest-posttest, and saturated sampling of all 19 students, psychomotor ability was measured across three indicators: conducting experiments, analyzing results, and presenting findings. The intervention yielded an N-gain score of 0.71, categorized as high, with notable improvements in conducting (0.89) and analyzing (0.92) experiments. Novelty: This study integrates hands-on experimental activities with structured psychomotor assessment, demonstrating the experimental method’s potential to bridge theory and practice in elementary science education. Implications: Findings highlight the importance of incorporating active, practice-oriented strategies in science curricula to foster holistic learning, suggesting that future research explore scalable, innovative models to sustain psychomotor development in primary education. Highlights: Significant improvement in psychomotor skills using experimental method. Highest gains in conducting and analyzing experiments. Supports active, hands-on learning in elementary science. Keywords: Experimental Method, Natural Science Learning, Psychomotor Skills, Elementary Education, 4th Grade Students